Effect of Teriparatide on Bone Mineral Density and Bone Markers in Real-Life: Argentine Experience. (13th January 2023) - Guelman, Rodolfo; Sánchez, Ariel; Varsavsky, Mariela; Brun, Lucas R.; García, María Laura; Sarli, Marcelo; Paula, Rey; Farias, Vanina; Zanchetta, María Belén; Giacoia, Evangelina; Salerni, Helena; Maffei, Laura; et al.
Abstract : Purpose . To evaluate the effect of teriparatide (TPTD) on bone mineral density (BMD) and bone markers under clinical practice conditions. To assess whether the results in real-life match those published in clinical trials. Methods . Cross-sectional study of postmenopausal women treated with TPTD for at least 12 months. Results . 264 patients were included in the study. Main characteristics are as follows: age: 68.7 ± 10.2 years, previous fractures: 57.6%, and previously treated with antiresorptive (AR-prior): 79%. All bone turnover markers studied significantly increased after 6 months. CTX and BGP remained high up to 24 months, but total and bone alkaline phosphatase returned to basal values at month 18. There was a significant increase in lumbar spine (LS) BMD after 6 months (+6.2%), with a maximum peak at 24 months (+13%). Femoral neck (FN) and total hip (TH) BMD showed a significant increase later than LS (just at month 12), reaching a maximum peak at month 24 (FN + 7.9% and TH + 5.5%). A significant increase in LS BMD was found from month 6 to month 24 compared to basal in both AR-naïve, and AR-prior patients (+16.7% and +10.5%, respectively), without significant differences between the two groups. Comparable results were found in FN and TH BMD. Main conclusions . As reported in real-life clinical studies, treatment of osteoporotic postmenopausal women with TPTD induced a significant increase in bone turnover markers from month 6 onward and an increase in BMD from months 6–12 with continuous gain up to month 24. The real-life results of our study matched the results of randomized clinical trials. In addition, TPTD induced an increase in BMD, regardless of the previous use of AR.